Single-Molecule Sequencing (PacBio) of the Staphylococcus capitis NRCS-A Clone Reveals the Basis of Multidrug Resistance and Adaptation to the Neonatal Intensive Care Unit Environment - Simões, Patrícia Martins; Lemriss, Hajar; Dumont, Yann; Lemriss, Sanâa; Rasigade, Jean-Philippe; Assant-Trouillet, Sophie; Ibrahimi, Azeddine; El Kabbaj, Saâd; Butin, Marine; Laurent, Frédéric (Frontiers in Microbiology, 2016)
The multi-resistant Staphylococcus capitis clone NRCS-A has recently been described as a major pathogen causing nosocomial, late-onset sepsis (LOS) in preterm neonates worldwide. NRCS-A representatives exhibit an atypical antibiotic resistance profile. Here, the complete closed genome (chromosomal and plasmid sequences) of NRCS-A prototype strain CR01 and the draft genomes of three other clinical NRCS-A strains from Australia, Belgium and the United Kingdom are annotated and compared to available non-NRCS-A S. capitis genomes. Our goal was to delineate the uniqueness of the NRCS-A clone with respect to antibiotic resistance, virulence factors and mobile genetic elements. We identified 6 antimicrobial resistance genes, all carried by mobile genetic elements. Previously described virulence genes present in the NRCS-A genomes are shared with the six non-NRCS-A S. capitis genomes. Overall, 63 genes are specific to the NRCS-A lineage, including 28 genes located in the methicillin-resistance cassette SCCmec. Among the 35 remaining genes, 25 are of unknown function, and 9 correspond to an additional type I restriction modification system (n=3), a cytosine methylation operon (n=2), and a cluster of genes related to the biosynthesis of teichoic acids (n=4). Interestingly, a tenth gene corresponds to a resistance determinant for nisin (nsr gene), a bacteriocin secreted by potential NRCS-A strain niche competitors in the gut microbiota. The genomic characteristics presented here emphasize the contribution of mobile genetic elements to the emergence of multidrug resistance in the S. capitis NRCS-A clone. No NRCS-A-specific known virulence determinant was detected, which does not support a role for virulence as a driving force of NRCS-A emergence in NICUs worldwide. However, the presence of a nisin resistance determinant on the NRCS-A chromosome, but not in other S. capitis strains and most coagulase-negative representatives, might confer a competitive advantage to NRCS-A strains during the early steps of gut colonization in neonates. This suggests that the striking adaptation of NRCS-A to the NICU environment might be related to its specific antimicrobial resistance and also to a possible enhanced ability to challenge competing bacteria in its ecological niche.